Review of Coherence in New Music: Experience, Aesthetics, Analysis, by Mark Hutchinson. (New York, NY: Routledge, 2016). - Orit Hilewicz (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2021)
A review of Mark Hutchinson's book from 2016, Coherence in New Music: Experience, Aesthetics, Analysis.
Keywords: Analysis; Multimodal experience; Contemporary Music; Twentieth-Century Composition